48.4k views
3 votes
How would you simplify this? Please help

How would you simplify this? Please help-example-1
User Gernot
by
4.6k points

2 Answers

4 votes

1.


\sqrt[3]{8^(4) }

2.


2 √(6) - 6 √(54) \\ 2 √(6) - 6 √(9 * 6) \\ 2 √(6) - 18 √(6) \\ - 16 √(6)

User Eric Geurts
by
4.0k points
1 vote


8^{(4)/(3)} = \sqrt[3]{8^4} = \sqrt[3]{(2^3)^4} = \sqrt[3]{2^(3*4)} = 2^4 = 16

Answer: C (16).


2√(6) - 6√(54) = 2√(6) - 2 * 3 * √(6) * √(9) = 2√(6)(1-3√(9)) = 2√(6)(1-3*3) = 2√(6)(1-9)=2*√(6)*(-8) = -16√(6)

User Matt Molnar
by
4.9k points